Correlating CT severity score and laboratory parameters in COVID-19 patients: the Indian experience - Singhal, Annu; Ramar, Raja Kumar; Kottiyath, Vivek C.; Gupta, Nishtha (International Journal of Research in Medical Sciences, 2022)
Background: Patients with COVID-19 infection present with myriad of symptoms to the clinicians. Many of these patients undergo HRCT chest and various lab tests during their treatment. Correlation between various lab parameters and severity of the disease on chest CT would be helpful in management of such patients. In situations where CT is not available, lab parameters may help to predict disease severity. The primary objective was to find out if there was any correlation between CT severity scores and laboratory parameters in patients having COVID-19 and if one can be extrapolated in cases where CT facilities may not be available. Methods: This is a retrospective, descriptive, and observational study. CT severity scores were obtained in all the patients using the 25 point scale. The following lab parameters were assessed: TLC, DLC, SGOT, SGPT, CRP, D-Dimer, IL-6, Serum Ferritin and serum LDH. Correlation was done between the CT score and various lab parameters using Pearson correlation coefficient test. Results: 285 patients with positive COVID-19 RT-PCR test were included in the study. CT score showed statistically significant positive correlation with age, TLC, Neutrophil count, SGOT, SGPT, CRP, D-dimer, IL-6, Ferritin and LDH with p-values less than 0.05. Negative correlation was seen with Lymphocyte count. Severe disease was found to be more common in older patients. Conclusions: In our study, CRP, LDH, Serum ferritin, IL-6 and D-dimer levels were observed to have positive correlation with disease severity on CT. Thus these measured at the time of admission can be taken into consideration to predict radiological severity.